Effectiveness of Cognitive Behavioral Therapy to Reduce Depression, Anxiety and Stress among Hospitalized Patients with Congestive Heart Failure in Central Java - Dian Hudiyawati; Ajie Maulana Prakoso (Universitas Airlangga, 2019)
Introduction: Psychological problems in patients with heart failure are the result of a combination of the influence of behavior and interactions with physiological responses, which if not handled properly will contribute to worsening clinical symptoms and have a higher risk of rehospitalization. The objective of the study was to evaluate the effects of cognitive behavior therapy (CBT) on psychological symptoms among CHF patients.Methods: This was a quasi-experimental, pretest-posttest control study that applying a CBT to overcome depression, anxiety, and stress. Thirty eligible respondents were recruited and were randomly divided into a case group and waiting list group. Psychological symptoms of respondents were measured using Depression, Anxiety and Stress Scale – 21 questionnaires (DASS-21). Chi-square was used to compare demographic data between groups and T-test analysis was used to describe changes in mean scores between and within groups. Both groups had similar characteristics and psychological symptoms level at baseline.Results: The mean score of depression, anxiety and stress showed a significant difference within the group after the intervention (p<0.05).Conclusion: A recent study found that CBT was effective to reduce psychological symptoms among CHF patients. Based on the study results it can be highlighted that it is important for nurses to provide brief CBT to hospitalized patients in an effort to reduce short term psychological symptoms.